PROSES DIFUSI INOVASI DAN KEPUTUSAN INOVASI SISTEM INFORMASI DESA: STUDI KASUS DI KABUPATEN LOMBOK TIMUR - Agus Purbathin Hadi; Diyah Indiyarti; Dian Lestari Miharja (Lampung University, 2019)
To realize the vision of the Village Law to make the village strong, independent, prosperous and democratic, the existence of a Village Information System (SID) becomes very important that the SID is specifically regulated in the Village Law. In 2017, the implementation of SID in East Lombok Regency has only been introduced in the Sub Districts of Terara and Aikmel. The objectives of this study are: (1) to analyze the SID diffusion process and innovation decisions, and (2) identify good practices for SID management learning. This research was conducted in 10 villages that carried out the SID program in East Lombok Regency. This study was designed as a qualitative descriptive study. Data collection through observation, FGD and in-depth interviews. The data analysis technique used is an interactive analysis model. The results of the study include: (1) Diffusion of innovations and SID innovation decisions takes place relatively quickly. The characteristic of the SID as needed, are more favorable, and support rediscovery. Communication channels use channels of mass communication, group communication, and interpersonal communication, where communication uses social media. The diffusion process occurs relatively quickly because of the existence of SID learning groups as a supportive social system; 2) Good practice for learning from SID management is the growth of initiatives from below to develop SID, the existence of SID forums and SID learning groups, and ongoing efforts to support the improvement of basic services (education, health, and population administration).Keywords: innovation decision, learning, diffusion process, Village Information System